Voluntary Disclosures and Analyst Feedback - LANGBERG, NISAN; SIVARAMAKRISHNAN, K. (Journal of Accounting Research, 2010)
ABSTRACT We study the resource allocation role of voluntary disclosures when feedback from financial markets is potentially useful to managers in undertaking value maximizing actions. Managers weigh the short‐term price implications of disclosure against the long‐term efficiency gains due to feedback while financial analysts strategically produce information. The model can explain why managers disclose bad information (e.g., grim outlook), that reduces the stock price, and why prices respond more strongly to bad news relative to good news. We find that not all firms enjoy the same quality of feedback, and that feedback, by itself, does not induce more disclosure but less .